2017
DOI: 10.22159/ijpps.2017v9i11.21924
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Evaluation of Titanium and Zinc Oxide Nanoparticles on Human Cell Lines

Abstract: Objective: In vitro cytotoxicity evaluation of titanium dioxide, 20 nm (TNP 20) and zinc oxide, 20 nm (ZNP 20) nanoparticles (NP) were tested on different types of human skin (HaCat), lung (A549), liver (Hep G2) and colon (Caco-2) cell cultures in relevance to human risk assessment Methods:The different concentrations of test TNP 20 and ZNP 20 1-300 µg/ml were exposed to determine the cell viability reduction on four human cell lines after 48 h post exposure using 3-(4, 5-dimethyl thiazol-2-yl)-2,5-diphenyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…TiO2 NPs is one of the most widely applied engineered nanoparticles in the nanotechnology field, where it is consequently used in paints, paper, plastics, ceramics, toothpaste, food colorants, drug capsule, catalysts and wastewater treatment [1,2]. The yearly production of TiO2 NPs in 2002 was approximately 3,000 tons per annum, and is estimated to increase to 2.5 million metric tons annually by 2025 [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TiO2 NPs is one of the most widely applied engineered nanoparticles in the nanotechnology field, where it is consequently used in paints, paper, plastics, ceramics, toothpaste, food colorants, drug capsule, catalysts and wastewater treatment [1,2]. The yearly production of TiO2 NPs in 2002 was approximately 3,000 tons per annum, and is estimated to increase to 2.5 million metric tons annually by 2025 [3].…”
Section: Introductionmentioning
confidence: 99%
“…The unique characteristics of TiO2 particle is that it can enter the human body quickly and then imposes potential health risks on human [6,7]. The adverse toxic effects of TiO2 NPs have been studied in several animal models like rats, mice, rabbits and human following exposure by multiple routes of administration, including whole-body exposure, dermal exposure, gastric lavage, and inhalation [1,2,8,9]. Few studies reported that inhaled or injected nanoparticles enter the systemic circulation and migrate to various parts to exert adverse effects [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the cytotoxicity of commercial TiO 2 NPs have been performed on different cell types but reported inconsistent results [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Differences in the cytotoxic effects of TiO 2 NPs in these published studies may be the result of several factors such as the type of TiO 2 NP, the type of cells used, the concentration of the tested range, etc.…”
Section: Resultsmentioning
confidence: 99%
“…These differences may have arisen from the different physicochemical properties of the tested samples, whether these were the particle size or surface chemistry of the particles. Several studies on the cytotoxicity of commercial TiO2 NPs have been performed on different cell types but reported inconsistent results [52][53][54][55][56][57][58][59][60]. Differences in the cytotoxic effects of TiO2 NPs in these published studies may be the result of several factors such as the type of TiO2 NP, the type of cells used, the concentration of the tested range, etc.…”
Section: Biological Propertiesmentioning
confidence: 99%
“…The effect of test nanocomposite hydrogel materials on the cellular proliferation and viability was determined using MTT assay method [69]. The biocompatibility of the prepared gels was determined by the following standard protocol with slight modifications [65].…”
Section: Resultsmentioning
confidence: 99%